2020
DOI: 10.1016/j.mtchem.2020.100283
|View full text |Cite
|
Sign up to set email alerts
|

BiVO4/TiO2 core-shell heterostructure: wide range optical absorption and enhanced photoelectrochemical and photocatalytic performance

Abstract: In the present study, pristine BiVO 4 , TiO 2 and BiVO 4 /TiO 2 core-shell heterostructured nanoparticles are prepared by hydrothermal methods and studied for structural, morphological, optical, photoelectrochemical water splitting and photocatalytic degradation of methylene blue as an organic pollutant. Both pristine BiVO 4 and TiO 2 exhibit poor PEC and PC performance under visible light illumination. However, an enhanced PEC and PC activity in BiVO 4 /TiO 2 core-shell heterostructure is observed due to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The optical band gap is calculated by the Tauc plot method as presented in Table 4 . 63 The reduction in optical bandgap results in an increase in the mobility of charge carriers, refractive index and electrical conductivity. 64,65 The results obtained are in accordance with those of previous work; 13,24,32,35 therefore, it is suggested that the prepared semiconductor material will also be very helpful for electronic device applications.…”
Section: Resultsmentioning
confidence: 99%
“…The optical band gap is calculated by the Tauc plot method as presented in Table 4 . 63 The reduction in optical bandgap results in an increase in the mobility of charge carriers, refractive index and electrical conductivity. 64,65 The results obtained are in accordance with those of previous work; 13,24,32,35 therefore, it is suggested that the prepared semiconductor material will also be very helpful for electronic device applications.…”
Section: Resultsmentioning
confidence: 99%
“…However, the full potential of BiVO 4 till date has not been realized yet due to various bottlenecks like slow water oxidation kinetics, small hole diffusion length, high electron–hole recombination rate, and photocorrosion . To achieve maximum efficiency, heteroatom doping, control of nanostructure morphology, and heterojunction formation with suitable band alignment are followed to cope with the limitations like small hole diffusion length and high electron–hole recombination rate, while oxygen evolution catalyst (OEC) overlayers are used to enhance otherwise sluggish water oxidation kinetics . Due to the sluggish oxidation process, photogenerated holes are consumed in the reactions with photoanode materials other than progressing for the oxygen evolution reactions (OERs) leading to photocorrosion of the materials, which limits the long-term stability of the photoanodes.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 For example, Mehta et al developed a BiVO 4 /TiO 2 heterostructure with an extended optical absorption range, showing improved photocatalytic activity compared to bare BiVO 4 . 40 Despite all of these efforts, the photocatalytic performance for the previously reported BiVO 4 / TiO 2 composites remained far from satisfactory because the simply combined components normally have a very limited contact interface and a relatively small surface area, which cannot provide sufficient channels for charge carrier transfer as well as sufficient sites for organic contaminant adsorption and reaction during the photocatalysis process. Herein, we designed and synthesized a unique core@porous-shell heterostructure composed of monoclinic scheelite BiVO 4 microellipsoid core and hierarchically nanostructured porous TiO 2 shell, which involves the in situ growth of TiO 2 nanosheets onto the uniform BiVO 4 microstructures by a facile hydrothermal method (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, TiO 2 , as the most widely used semiconductor, has advantages of excellent stability, high activity, low cost, and nontoxic nature. Thus, various BiVO 4 /TiO 2 systems have been developed for photocatalysis. , For example, Mehta et al developed a BiVO 4 /TiO 2 heterostructure with an extended optical absorption range, showing improved photocatalytic activity compared to bare BiVO 4 . Despite all of these efforts, the photocatalytic performance for the previously reported BiVO 4 /TiO 2 composites remained far from satisfactory because the simply combined components normally have a very limited contact interface and a relatively small surface area, which cannot provide sufficient channels for charge carrier transfer as well as sufficient sites for organic contaminant adsorption and reaction during the photocatalysis process.…”
Section: Introductionmentioning
confidence: 99%